Penyuluhan Dagusibu Sebagai Upaya Meningkatkan Pengetahuan Siswa SMP Tentang Penyimpanan Obat Berdasarkan Bentuk Sediaan - Hindri Syahputri; Yusnita Putri Marpaung; Zahrima Dwi Ananda Lubis; Nadia Pasaribu; Putri Aulia; Khoirul Ummi Nur’ailah Surbakti (Universitas Pahlawan Tuanku Tambusai, 2026)
Improper medication storage can compromise a drug's quality, stability, safety, and effectiveness, potentially diminishing its therapeutic benefits. Therefore, early education on the proper acquisition, use, storage, and disposal of medicines—specifically through the DAGUSIBU program (an acronym for *Dapatkan, Gunakan, Simpan, dan Buang Obat dengan Benar* or